STRATEGI DAKWAH PEMERINTAH DESA DALAM MENCEGAH PEREDARAN NARKOBA DI DESA TAMATTO KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The da'wah strategy carried out by the village government is by using sentimental and rational da'wah strategies, as for efforts in da'wah strategies sentimental, namely by giving advice, cooperation with organizations' youth, parental approaches, and sports coaching. Then in a rational strategy, namely by conducting anti-drug education, The supporting factors are the existence of youth organizations and their roles as parents, while the inhibiting factor is the existence of a negative environment and technology abuse. The implications of this research are: For the village government should continue to make prevention efforts in drug trafficking in the village, and the community should be actively involved in every activity effort made by the government in preventing the occurrence of circulation of drugs in the village. For parents should continue to perform the role and responsibility of ensuring the future of their children so that stay away from drugs.